The Ottoman Endgame : War, Revolution and The Making of the Modern Middle East, 1908-1923 - McMeekin, Sean (New York Penguin Press, 2015)
Features the history of the Ottoman empire's decade-long war for survival. Beginning with Italy's invasion of Ottoman Tripoli in September 1911, the opening salvo in what would soon spiral into a European conflict, this book concludes with the establishment of Turkish independence in the Treaty of Lausanne, 1923.
Include Illustrations, Bibliography and Index
Keywords: Turkey -- Middle East -- Politics and government